2019
DOI: 10.1029/2019jf005156
|View full text |Cite
|
Sign up to set email alerts
|

Model for the Formation of Single‐Thread Rivers in Barren Landscapes and Implications for Pre‐Silurian and Martian Fluvial Deposits

Abstract: Flume experiments and field observations show that bank vegetation promotes the formation of narrow and deep single‐thread channels by strengthening riverbanks. Consistent with this idea, the pre‐Silurian fluvial record generally consists of wide monotonous sand bodies often interpreted as deposits of shallow braided rivers, whereas single‐thread rivers with muddy floodplains become more recognizable in Silurian and younger rocks. This shift in the architecture of fluvial deposits has been interpreted as refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 141 publications
(306 reference statements)
1
49
0
Order By: Relevance
“…The abundance of mudstone in the studied outcrop here is not known or speculated upon, as their intrinsic fine-grained components require rover-based observations. However, the preserved channel-belt architecture, comprising relatively intact channels and barforms, suggests some degree of original channel-belt stability, with naturally shear-resistant sediment such as mud a possible candidate 47,48 . With regard to channel and barform facies, evidence of relatively stable, deep-channelled drainage on pre-vegetation Earth is being increasingly reported 37 .…”
Section: Resultsmentioning
confidence: 99%
“…The abundance of mudstone in the studied outcrop here is not known or speculated upon, as their intrinsic fine-grained components require rover-based observations. However, the preserved channel-belt architecture, comprising relatively intact channels and barforms, suggests some degree of original channel-belt stability, with naturally shear-resistant sediment such as mud a possible candidate 47,48 . With regard to channel and barform facies, evidence of relatively stable, deep-channelled drainage on pre-vegetation Earth is being increasingly reported 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Martian sinuous ridges have long been interpreted as remnants of meandering channel belts (e.g., Burr et al, 2006Burr et al, , 2010Cardenas et al, 2018;DiBiase et al, 2013;Kite et al, 2015;Williams, Irwin, et al, 2013). Although adjoining floodplain materials appear to have been eroded, as commonly observed in inverted fluvial landscapes on Earth (e.g., Hayden et al, 2019), river flows were most likely confined by banks that contained fine-grained materials (e.g., Lapôtre et al, 2019). Clay minerals have been detected globally on Mars by orbiting spectrometers (e.g., Ehlmann & Edwards, 2014;Mustard et al, 2008;Poulet et al, 2005), including within delta deposits (e.g., Ehlmann et al, 2008;Goudge et al, 2015).…”
Section: Single-thread Rivers On Mars: Scaling For Martian Gravitymentioning
confidence: 99%
“…Therefore, the empirical calibration of migration rates is typically performed on a case-by-case basis (e.g., Matsubara & Howard, 2014). While vegetation plays a critical role in bank stabilization (e.g., Braudrick et al, 2009;Davies & Gibling, 2010;Parker et al, 2011;Smith, 1976), recent field and modeling studies demonstrated the stability of single-thread rivers in unvegetated or sparsely vegetated basins (Ielpi, 2019;Ielpi & Lapôtre, 2019a, 2019bLapôtre et al, 2019;Li et al, 2015;Matsubara et al, 2015;Santos et al, 2017Santos et al, , 2019. Because their morphodynamics are unaffected by plant life, modern unvegetated single-thread rivers may offer particularly relevant analogs for ancient Martian single-thread rivers.…”
Section: Lateral Migration Of Terrestrial Single-thread Riversmentioning
confidence: 99%
“…Some efforts have centred on connecting landscape surface kinematics to stratal preservation (Paola & Borgman, 1991;Castelltort & Van Den Driessche, 2003;Jerolmack & Mohrig, 2005;Jerolmack & Paola, 2010;Hajek & Wolinsky, 2012;Ganti et al, 2013;Ganti et al, 2014;Reesink et al, 2015;Romans et al, 2016;Ganti et al, 2020;Straub et al, 2020) and a number of these studies have focused on Late Cretaceous fluvial strata in central Utah Trower et al, 2018;Ganti et al, 2019a). Meanwhile, other quantitative work has applied fluid and sediment transport models to stratigraphic field data, with an overarching goal of constraining the characteristics of catchments, regional systems or entire fluvial landscapes in the geological past (Ganti et al, 2019b;Lapôtre et al, 2019), or even on other planetary bodies (Lamb et al, 2012;Buhler et al, 2014;Hayden et al, 2019;Lapôtre et al, 2019). This includes using quantitative palaeohydrological tools to reconstruct water and sediment discharges within mass balance frameworks (Holbrook & Wanas, 2014;Lin & Bhattacharya, 2017;Sharma et al, 2017), decipher local palaeogeographies (Bhattacharyya et al, 2015;Li et al, 2018), characterise pre-vegetation rivers (Ganti et al, 2019b), and reconstruct fluvial response to climatic perturbations for well-preserved fluvial strata straddling events such as the Paleocene-Eocene Thermal Maximum (PETM) (Foreman et al, 2012;Foreman, 2014;Colombera et al, 2017;Chen et al, 2018;Duller et al, 2019).…”
Section: (A) Research Background (B) Palaeohydrologymentioning
confidence: 99%